Polyphasic Analysis of Intraspecific Diversity in Epicoccum nigrum Warrants Reclassification into Separate Species - Fávaro, Léia Cecilia de Lima; de Melo, Fernando Lucas; Aguilar-Vildoso, Carlos Ivan; Araújo, Welington Luiz (PLOS ONE, 2011)
Background Epicoccum nigrum Link (syn. E. purpurascens Ehrenb. ex Schlecht) is a saprophytic ascomycete distributed worldwide which colonizes a myriad of substrates. This fungus has been known as a biological control agent for plant pathogens and produces a variety of secondary metabolites with important biological activities as well as biotechnological application. E. nigrum produces darkly pigmented muriform conidia on short conidiophores on sporodochia and is a genotypically and phenotypically highly variable species. Since different isolates identified as E. nigrum have been evaluated as biological control agents and used for biocompound production, it is highly desirable that this species name refers to only one lineage. However, according to morphological and genetic variation, E. nigrum present two genotypes that may comprise more than one species. Methodology/Principal Findings We report the application of combined molecular (ITS and β-tubulin gene sequence analysis, PCR-RFLP and AFLP techniques), morphometric, physiological, genetic compatibility and recombination analysis to study the taxonomic relationships within an endophytic population that has been identified as E. nigrum. This combined analysis established two genotypes showing morphological, physiological and genetic divergence as well as genetic incompatibility characterized by colony inhibition, strongly indicating that these genotypes correspond to different species. Genotype 1 corresponds to E. nigrum while genotype 2 represents a new species, referred to in this study as Epicoccum sp. Conclusions/Significance This research contributes to the knowledge of the Epicoccum genus and asserts that the classification of E. nigrum as a single variable species should be reassessed. In fact, based on the polyphasic approach we suggest the occurrence of cryptic species within E. nigrum and also that many of the sequences deposited as E. nigrum in GenBank and culture collection of microbial strains should be reclassified, including the reference strain CBS 161.73 sequenced in this work. In addition, this study provides valuable tools for differentiation of Epicoccum species.